Association of ambient particulate matter pollution and stroke in Indonesia 2011-2020: Insights from the global burden of disease study 2021 - Salma Dhiya Rachmadani (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Ambient particulate matter ≤2.5 μm (PM2.5) is a major environmental health risk contributing to global morbidity and mortality. Although its link with cardiovascular diseases is well established, evidence on the stroke burden attributable to PM2.5 exposure remains limited in Indonesia. Methods: This ecological study used Global Burden of Disease (GBD) 2021 data to analyze the association between PM2.5 exposure and stroke burden, including incidence, prevalence, and mortality, across 34 Indonesian provinces from 2011 to 2020. Age-standardized rates (ASRs) were assessed using a linear mixed model, with year as a repeated measure and province as a random effect to account for spatial and temporal variations. Findings: Mean PM2.5 concentrations ranged from 16.96 to 20.10 µg/m³, exceeding WHO and national air quality standards. Despite minor annual fluctuations in PM2.5, stroke mortality attributable to air pollution showed an increasing trend. Higher PM2.5 levels were significantly associated with ischemic stroke (IS) incidence (β = -0.117, p <0.001) and mortality (β = 0.152, p <0.001), as well as intracerebral hemorrhage (ICH) incidence (β = 0.017, p = 0.015), prevalence (β = 1.641, p <0.001), and mortality (β = 0.773, p = 0.004). The effect of PM2.5 exposure was greater for ICH than for IS. Conclusion: Long-term exposure to PM2.5 is significantly associated with stroke burden in Indonesia, particularly for ICH. Strengthening air quality management and stroke prevention policies is crucial, especially in high-risk regions. Novelty/Originality of this article: This study is the first to comprehensively assess the long-term association between PM2.5 and stroke subtypes using national-level GBD data across all Indonesian provinces, providing spatially and temporally robust evidence for public health policy in low- and middle-income tropical settings.